Binuclear Copper(II) Complexes Containing Two Crown-Type Macrocyclic Rings - Keypour, Hassan; Salehzadeh, Sadegh (Asian Journal of Chemistry, 2010)
In the presence of copper(II) two hexadentate amines 1,3- and 1,4-bis[bis(3-aminopropyl)]-benzene condenses with 2,6-diacetylpyridine in ethanol-water solution (1: 1), producing binuclear Schiff-base macrocycles. The effective magnetic moments of each copper atom in solution for these complexes are about 1.75 B.M., indicating that the two macrocyclic rings are probably in face-to-face fashion and some antiferromagnetic interaction is operative between the two copper(II) ions. IR and UV-VIS spectra of these complexes are also studied.